Epidemiology, virology and clinical aspects of hantavirus infections: an overview. Issue 8 (3rd August 2022) - Singh, Sima; Numan, Arshid; Sharma, Dinesh; Shukla, Rahul; Alexander, Amit; Jain, Gaurav Kumar; Ahmad, Farhan Jalees; Kesharwani, Prashant
ABSTRACT: At the end of 2019 and 2020s, a wave of coronavirus disease 19 (COVID-19) epidemics worldwide has catalyzed a new era of 'communicable infectious diseases'. However, the world is not currently prepared to deal with the growing burden of COVID-19, with the unexpected arrival of Hantavirus infection heading to the next several healthcare emergencies in public. Hantavirus is a significant class of zoonotic pathogens of negative-sense single-stranded ribonucleic acid (RNA). Hemorrhagic renal syndrome (HFRS) and hantavirus cardiopulmonary syndrome (HCPS) are the two major clinical manifestations. Till date, there is no effective treatments or vaccines available, public awareness and precautionary measures can help to reduce the spread of hantavirus disease. In this study, we outline the epidemiology, virology, clinical aspects, and existing HFRS and HCPS management approaches. This review will give an understanding of virus-host interactions and will help for the early preparation and effective handling of further outbreaks in an ever-changing environment.